Enhancing ePaper Reader Intentions through Website Design, Information Quality, and Usefulness - Amiril Azizah; Surahman; Ahyar M. Diah; Kiswanto; Muhammad Naufal (Jurnal Dinamika Manajemen, 2024)
This study examines how website design, information quality, and utility affect ePaper use, with brand trust and attitude as mediators. This study examines the factors that influence ePaper readers’ intentions to use the service. The quantitative study uses a survey questionnaire to collect data. A convenience sample of ePaper readers was selected. Structural Equation Modelling (SEM) was used to analyses data and determine variable relationships. The study found that website design, information quality, and usability affect brand trust, attitude, and ePaper use. A well-designed website with high-quality information and handy features boosts brand trust and attitude, which affects ePaper service use. This study adds to the literature by examining the relationships between website design, information quality, utility, brand trust, attitude, and ePaper use. The results suggest that ePaper suppliers should priorities website design, high-quality content, and useful features to build brand confidence and reader loyalty. It will boost their desire to use the service. Future investigations should aim to examine the potential effects of supplementary variables that could potentially influence individuals’ intents to utilized ePaper, including those related to user experience and social dynamics.